Meninjau Keabsahan Hak Guna Bangunan PT Indobuildco di Kawasan Gelora Senayan - I Gede Yudi Arsawan; Ignatius Pradipa Probondaru (Kertha Wicaksana, 2026)
The polemic over land control in the Gelora Senayan area on the HGB held by PT Indobuildco and the HPL granted to the State Secretariat of the Republic of Indonesia raises fundamental issues concerning the legality of rights acquisition and legal certainty for the right holder. This research aims to examine the validity of HGB No. 26/Gelora and No. 27/Gelora and to analyze the legal consequences of the issuance of HPL over land on which HGB had been granted earlier. This study employs a normative juridical method with a statutory approach and a case approach, through an examination of land law regulations, legal doctrines, and relevant court decisions. The findings indicate that the granting of HGB to PT Indobuildco in 1972 satisfied the requirements of authority, procedure, and substance; therefore, the rechtstitel underlying the issuance of the HGB was valid and should provide legal protection to the rights holder. Furthermore, the issuance of HPL in 1989 over land that was still encumbered by valid HGB was, in principle, inconsistent with the systematic structure of national land law and contrary to the principle of legal certainty. As long as the HGB remains in force and fulfills the requirements for extension, the state may not unilaterally nullify or set aside such rights through administrative instruments in the form of HPL. Instead, there must first be a lawful mechanism of revocation or release of rights accompanied by compensation for the state to reacquire the land.